Long Non-Coding RNAs in Epithelial-Mesenchymal Transition of Pancreatic Cancer - Takahashi, Kenji; Taniue, Kenzui; Ono, Yusuke; Fujiya, Mikihiro; Mizukami, Yusuke; Okumura, Toshikatsu (Frontiers in Molecular Biosciences, 2021)
Non-coding RNAs (ncRNAs), or RNA molecules that do not code for proteins, are generally categorized as either small or long ncRNA (lncRNA) and are involved in the pathogenesis of several diseases including many cancers. Identification of a large number of ncRNAs could help to elucidate previously unknown mechanisms in phenotype regulation. Some ncRNAs are encapsulated by extracellular vesicles (EVs) and transferred to recipient cells to regulate cellular processes, including epigenetic and post-transcriptional regulations. Recent studies have uncovered novel molecular mechanisms and functions of lncRNAs in pancreatic ductal adenocarcinoma (PDAC), one of the most intractable cancers that is highly invasive and metastatic. As the epithelial-mesenchymal transition (EMT) triggers tumor cell invasion and migration, clarification of the roles of lncRNA in EMT and tumor cell stemness would be critical for improving diagnostic and therapeutic approaches in metastatic cancers. This review provides an overview of relevant studies on lncRNA and its involvement with EMT in PDAC. Emerging knowledge offers evidence for the dysregulated expression of lncRNAs and essential insights into the potential contribution of both lncRNAs and EVs in the pathogenesis of PDAC. Future directions and new clinical applications for PDAC are also discussed.